Nonlinear model of stock price dynamics with behavioural functions - Illichmann, Vít (2021)
The thesis investigates the relation between inefficient processing of objective probability proposed by the Prospect theory and excess volatility present in stock market prices. The author employs an agent-based model to show the destabilizing influence of the cognitive bias in question with a positive result. For a high level of distortions in probability perception, the model produces chaotic oscillations in price with the fundamental value of shares held fixed. The secondary focus is on the explanation of the origin of the proposed behaviour, which the author attributes to the biological restrictions present in the process of cognitive evolution.